Recapturing lost values - Caribbean literature in the Caribbean classroom - Pollard, Velma (My University, 1992)
Caribbean literature has been used in the Caribbean classroom largely as content for developing critical and analytical skills in students. The human/humane content of the material has, to a large extent, been underplayed. This paper contends that a hidden resource for the teaching of values, now at risk in these societies, has remained unexploited. It examines two short stories and indicates how they might be used in the classroom as triggers for bringing specific values to the attention of young people. It is suggested that if the artist is the conscience of the society, this is one way in which she/he might profitably be used.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992
Keywords: Caribbean literature